2012
DOI: 10.4068/cmj.2012.48.2.128
|View full text |Cite
|
Sign up to set email alerts
|

Hypercalcemia in a Patient with Polycythemia Vera

Abstract: A 59-year-old female with diabetes mellitus presented with hypercalcemia and polycythemia. Her serum calcium and intact parathyroid hormone (iPTH) levels were increased, and Tc-99m sesta-MIBI scanning showed hot uptake in the lower portion of the left thyroid lobe. After parathyroidectomy, her calcium, iPTH, and polycythemia were normalized. In conclusion, the differential diagnosis of polycythemia and hypercalcemia should also include the possibility of a parathyroid tumor in addition to other neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Although this evidence provides an explanation for the mechanism of dual-phase 99m Tc-MIBI parathyroid imaging, it is likely that other factors are involved. As preoperative localization of abnormal parathyroid glands by dual-phase 99m Tc-MIBI imaging may improve patient outcomes and reduce the duration and cost of surgery for HPT, further investigations are warranted 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Although this evidence provides an explanation for the mechanism of dual-phase 99m Tc-MIBI parathyroid imaging, it is likely that other factors are involved. As preoperative localization of abnormal parathyroid glands by dual-phase 99m Tc-MIBI imaging may improve patient outcomes and reduce the duration and cost of surgery for HPT, further investigations are warranted 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Hypercalcemia occurring by different mechanisms has been reported in association with polycythemia vera. Several studies have reported an association between polycythemia vera and primary hyperparathyroidism, with resolution of polycythemia following surgical removal of a parathyroid adenoma or a parathyroid carcinoma . These reports antedate JAK2 mutation testing, and these patients may possibly not have had polycythemia vera, but rather secondary polycythemia, with the parathyroid lesions possibly stimulating or secreting erythropoietin.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported an association between polycythemia vera and primary hyperparathyroidism, with resolution of polycythemia following surgical removal of a parathyroid adenoma or a parathyroid carcinoma. [5][6][7][8] These reports antedate JAK2 mutation testing, and these patients may possibly not have had polycythemia vera, but rather secondary polycythemia, with the parathyroid lesions possibly stimulating or secreting erythropoietin. An association between parathyroid adenomas and polycythemia vera was identified in a historical cohort study, 9 but it is again unclear whether these cases represented polycythemia vera or secondary polycythemia.…”
Section: Discussionmentioning
confidence: 99%
“…The parathyroid tumour may have produced or induced the production of a growth factor that can stimulate pancytosis. [ 7 ] Tiryakioglu et al . suggested that the calcium-PTH axis is important for the activation of erythropoiesis.…”
mentioning
confidence: 99%